PENGARUH EKSTRAK DAUN SIRSAK (Annona muricata Zinn) TERHADAP PERKEMBANGAN LARVA Aedes aegypti - Susiwati, Susiwati (JURNAL MEDIA KESEHATAN, 2015)
Soursop plants is a plant that is widely available in Indonesia. In addition tofruit that can be directly consumed. The main content of soursop is active compounds annonaceusacetogenin. The leaves are most part annonaceus acetogenin containing compoundsthat are known to have the effect of insecticide, antifeedant repelant and works as acontact and stomach poison toxin in Aedes aegypti larvae. The purpose of this study was todetermine the effect of extract of soursop’s leaves (Annona muricata Zinn) as larvicides ofAedes aegypti in different levels of concentrations. This research is quasi-experimental. Thesamples used were 600 instar larvae of Aedes aegypti III/IV. Each treatment containing 25larvae and repetition as much as 4 times. Soursop leaf extract concentration tested, namely 0%(control), 5%, 10%, 15%, 20%, and 25%. The result is the number of Aedes aegypti larvaewere dead after 24 hours in each concentration group. Greatest death in a concentration of25% is as much as 92%, while the lowest mortality at a concentration of 5% is as much as15%. The results of the study were further tested with One Way Anova. Statistical test resultsobtained with One Way Anova sig. = 0.000 so that ρ < α (0.05) means that there is a significanteffect on the difference in average number of larvae mortality in each treatment groupbecause of increasing the concentration. LSD test results showed a mean difference significantat the 0.05 level. From the results of this research community can use extract of soursop’sleaves with a concentration of 25% as an alternative to eradication of Aedes aegypti is a vectorof Dengue Fever (DHF). Further research needs to be done on the toxicology and safety ofsoursop leaf extract as an alternative to the eradication of Aedes aegypti mosquito larvae